Dst Index Forecast Based on Ground‐Level Data Aided by Bio‐Inspired Algorithms - Lazzús, J. A.; Vega‐Jorquera, P.; Palma‐Chilla, L.; Stepanova, M. V.; Romanova, N. V. (Space Weather, 2019)
In this study, different hybridized techniques that combine an artificial neural network (ANN) with bio‐inspired optimization algorithms such as particle swarm optimization (PSO), genetic algorithm (GA), and a hybridized PSO+GA were applied to update the ANN connection weights and so forecast the disturbance storm time (Dst) index. The past values of Dst index time series were used as input parameters to forecast its variation from 1 to 6 hours ahead. The database collected considers 233,760 hourly data from 01 January 1990 to 31 August 2016, containing storms and quiet period, grouped into three data sets: learning set (116,880 hourly data points), validation set (58,440 data points), and testing set (58,440 data points). Several ANN configurations were studied and optimized during the training process by evaluating the root mean square error (RMSE) and the correlation coefficient (R). An analysis of the predictive capability of each method was made year per year, and according to the levels of the geomagnetic storm. Also, an additional test was applied to the proposed method using 17 intense geomagnetic storms reported during solar cycle 24, including the St. Patrick's Day storm of 2015. Results show that the hybridized ANN+PSO method can forecast the Dst index quite accurately from 1 to 3 h in advance (with RMSE≤5 nT and R≥0.9), while the ANN+PSO+GA method can forecast the Dst index quite accurately from 4 to 6 h ahead (RMSE≤7 nT and R≥0.8) Key Points Dst index was forecasted from 1 to 6 hours ahead using only prior values Three bio‐inspired algorithms combining neural networks (ANN), particle swarm optimization (PSO) and genetic algorithms (GA) were used Data from 17 intense storms reported in solar cycle 24 were used to evaluate the proposed methods